Effect of Brassica Oleraceae on Nematodes Meloidogyne Spp., Parasites of Tomato, in Yamoussoukro in the Center Côte D'ivoire - KAKOU, Didier Junior; Yeo, Gnénakan; N’guessan, Aya Carine; Elisée, Amari Ler-N’ogn Dadé Georges; Camara, Brahima; Abo, Kouabenan; Kone, Daouda (European Journal of Applied Sciences, 2022)
Tomatoes, which are still a highly prized commodity in Côte d'Ivoire, are subject to significant pest pressure from viral diseases, bacterial diseases and pests such as Meloidogyne spp. Tolerant varieties have been identified in the Yamoussoukro region of central Côte d'Ivoire. However, the yields obtained, Mongal (3437.5 kg/ha; 4438.75 kg/ha) and F1 Cobra 26 (2412.5 kg/ha; 2973 kg/ha) were average given the influence of these nematodes on production 1. In order to control these pests and improve the yield of ten tomato varieties by alternative control methods to synthetic pesticides, a study on the use of brassicas as a service plant was conducted in the Yamoussoukro region. The trial design was a randomised complete Fisher block design. Observations were made on agronomic parameters, nematological parameters and yield components. The results of this study revealed an increase in yield of all tomato varieties grown after the passage of brassicas as intercrop; that is 3737.50 kg/ha to 12237 kg/ha for net yield and 4305 kg/ha to 14175 kg/ha for potential yield. This yield increase is the result of the nematicidal effect of Brassicas. However, the best tomato varieties remain Mongal (12237.50 kg/ha; 14175 kg/ha) and F1 Cobra 26 (8150 kg/ha; 9962.50 kg/ha).